THE EFFECT OF SENSORIMOTOR GAMES ON INCREASING LEARNING CONCENTRATION OF EXPORT TRAINING PARTICIPANTS AT ASI TRAINING CENTER BEKASI CITY, WEST JAVA - Aminoto, Toto; Agustina, Dwi (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Concentrating on the lesson is essential to absorb the lesson material export provided by the facilitator. In this way, it is hoped that training participants during the competency exam will be able to answer the questions quickly. One form of effort to increase concentration is sensorimotor games. This research aims to prove sensorimotor games' influence on trainees' learning concentration at the ASI Training Center in Bekasi City. The benefit of this research is that physiotherapy wants to demonstrate the effect of sensorimotor games on training participants' learning concentration. By concentrating, you get better learning results. The sampling technique used was purposive sampling. This group was divided into two research groups. Treatment group with intervention and control group without intervention. Each group consisted of 15 respondents. Statistical analysis used the independent t-test. The results showed that there were differences between the control group and the treatment group. These results show that the treatment group scored higher than the control group. Thus, the treatment group was more effective than the control group. So, it is supposed that sensorimotor games influence the level of learning concentration.